PENGARUH SHORT COURSE DI NANCHANG NORMAL UNIVERSITY TERHADAP KEMAMPUAN BAHASA MANDARIN MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA MANDARIN UNIVERSITAS NEGERI MAKASSAR - Jasmita, Jasmita; Syarifah Fathimah Al Ilmullah; azizah, mir'ah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the short course program at Nanchang Normal University on the development of Mandarin language skills of students in the Mandarin Language Education Study Program at UNM. This research employs a quantitative descriptive method with a pre-test and post-test experimental design. The data were collected by measuring students’ Mandarin language proficiency before and after participating in the program. The results show that prior to joining the short course, students’ Mandarin proficiency was at a moderate level and not yet optimal, particularly in speaking and writing skills, which were still weak in terms of vocabulary mastery and sentence structure. After completing the program, students’ proficiency improved to a good level, with the average score increasing from 108.18 to 158.91. This improvement is reflected across all four language skills, especially in listening and speaking. The results of the paired sample t-test indicate a significance value of 0.001 (< 0.05), meaning that the short course program has a significant effect on students’ Mandarin language proficiency. Therefore, the short course program is proven to be effective in improving Mandarin language skills and can be recommended for curriculum development and academic policy at UNM.